Effects of erdosteine on inflammation and fibrosis in rats with pulmonary fibrosis induced by bleomycin - Erden, Ersin Sukru; Kirkil, Gamze; Deveci, Figen; Ilhan, Nevin; Cobanoglu, Bengu; Turgut, Teyfik; Muz, Mehmet Hamdi (Turkish Assoc Tuberculosis & Thorax, 2008)
We aimed to investigate the levels of some chemokines, inflammatory cell counts in bronchoalveolar lavage (BAL) fluid, histopathological changes in lung tissue, to determine the effect of erdosteine on acute inflammatory changes and fibrosis in a rat fibrosis model induced by bleomycine (BLM). Forty-five Wistar male rats were taken into the study. On day 0, intratracheal saline to control group (group 1, n= 15), intratracheal BLM 7.5 U/kg to BLM (group 2, n= 15) and erdostein group (group 3, n= 15) was administered. In group 3, oral erdostein (10 mg/kg/day) was applied two days before BLM. On day 0, 14, and 29th five rats in each groups were sacrificed, BAL fluid was performed. Malonyldialdehyde (MDA), macrophage inflammatory protein (MIP)-1 alpha, MIP-2 levels in BAL fluid, hydroxyproline levels in lung tissue were measured. Histopathological examination was performed. When BLM group compared to erdostein group, the levels of MDA, MIP-1 alpha, MIP-2, and neutrophil counts, the hydroxyproline (OH-P) level of lung tisssue were decreased in erdostein group on acute inflammatory phase (day 14) (p< 0.001, p= 0.017, p= 0.009, p< 0.001, p= 0.009, respectively), and late fibrosis phase (day 29) except BAL MIP-2 (p= 0.022, p= 0.025, p= 0.01, p< 0.001, respectively). Fibrosis level was significantly lower in erdostein group than BLM group on day 29 ( p= 0.01). We conclude that erdostein may prevent the acute lung inflammation and fibrosis by supressing the accumulation of neutrophils, inhibition of lipid peroxydation, chemokine production, and release.
Ratlarda bleomisin ile olušturulan akci?er fibrozisinde erdosteinin inflamasyon ve fibrozis üzerine etkileri
Keywords: Lung fibrosis; MDA; MIP-1a; MIP-2; hydroxyproline; erdostein